2011
DOI: 10.1021/ol2022438
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Imidazolones and 2-Iminoimidazoles

Abstract: Convenient methods for the direct conversion of imidazolium salts to the corresponding 2-imidazolone or 2-imino imidazole derivatives have been developed. Treatment of the salt with commercial bleach leads to effective oxidation at C2 and the formation of the corresponding imidazolone. Alternatively, treatment of the salt with an N-chloro amide affords the corresponding protected 2-amino derivative in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…12 Our data are also consistent with the synthesis of the 2-oxo form, in particular an absorption at 154.8 ppm in the 13 C NMR spectrum is characteristic for a 2-imdazolone. 22 Careful comparison of the 13 C NMR data obtained by us and the Ohta lab indicated that one signal at 145.2 ppm was missing and an extra absorbance appears at 126.5 ppm in the Ohta report. In the course of our studies towards the kealiiquinone group of molecules we have prepared two other kealiiquinone-like structures 11 and 12 via a completely different strategy involving an intramolecular Diels-Alder reaction and we find that the 13 C NMR data are an excellent match for 1 (Table 2).…”
mentioning
confidence: 90%
“…12 Our data are also consistent with the synthesis of the 2-oxo form, in particular an absorption at 154.8 ppm in the 13 C NMR spectrum is characteristic for a 2-imdazolone. 22 Careful comparison of the 13 C NMR data obtained by us and the Ohta lab indicated that one signal at 145.2 ppm was missing and an extra absorbance appears at 126.5 ppm in the Ohta report. In the course of our studies towards the kealiiquinone group of molecules we have prepared two other kealiiquinone-like structures 11 and 12 via a completely different strategy involving an intramolecular Diels-Alder reaction and we find that the 13 C NMR data are an excellent match for 1 (Table 2).…”
mentioning
confidence: 90%
“…Elemental analysis was carried out on a PerkinElmer Series-II CHNS/O Analyzer 2400. General Procedure of synthesis Synthesis of 4-bromophenoxy acetic acid (2) To the solution of 4-bromophenol (1.0 eq.) in acetone (8 vol) was added potassium carbonate (1.5 eq.)…”
Section: Methodsmentioning
confidence: 99%
“…The benzimidazole nucleus, which is a useful structure for research and development of new pharmaceutical molecules, Benzimidazoles are among the important heterocyclic compounds found in several natural and non-natural products such as vitamin B 12 1 , marine alkaloid kealiiquinone 2 , and benzimidazole nucleosides 3 etc. Some of the benzimidazole derivatives are marketed as anti-fungal 4 , anti-helmintic 5 and anti-psychotic 6 drugs and other derivatives have been found to possess some interesting bioactivities such as antitubercular 7 , anti-cancer 8 , HIV-Inhibitors 9 , Anti-Hypertensive Agent 10 , Anti-Inflammatory activity 11 , Anti-allergic activity 12 , Anti-diabetic Activity 13 , Anticonvulsant activity 14 and DNA Inhibitory Activity 15 etc.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] However, this procedure requires several steps, and has failed in the synthesis of some natural products, such as kealiiquinone. 27 To solve these problems, Lovely group has recently developed a convenient procedure for the direct conversion of imidazolium salts into 2-aminoimidazoles by using Nchloroamides at room temperature. 27 On the other hand, the synthesis of biologically active imidazolines, such as clonidine and indanazoline has been developed by Cussac et al through the condensation between primary amines and imidazolidin-2-ones or 2-methylsulfanyldihydroimidazoles.…”
Section: Figurementioning
confidence: 99%
“…27 To solve these problems, Lovely group has recently developed a convenient procedure for the direct conversion of imidazolium salts into 2-aminoimidazoles by using Nchloroamides at room temperature. 27 On the other hand, the synthesis of biologically active imidazolines, such as clonidine and indanazoline has been developed by Cussac et al through the condensation between primary amines and imidazolidin-2-ones or 2-methylsulfanyldihydroimidazoles. [28][29][30][31] Other procedures involve the condensation of amines with dihydroimidazol-3-ium-2-sulfonate 32 or with protected imidazolidine-2-thione, though the last procedure requires the use of mercury (II) chloride.…”
Section: Figurementioning
confidence: 99%